(untitled) (LACCEI, 2024)
The goal of this work is to characterize the effect of barriers and factors in the creation of New Technology-Based Companies by women entrepreneurs in the state of Atlántico. In the same way, the key barriers, and obstacles that women perceive when participating in entrepreneurship activities, business development and/or creation of technology-based companies were identified, and likewise, the main factors were analyzed that affect female technological entrepreneurship. This research was based primarily on a review of the literature, exploring the different theoretical perspectives and contributions to the knowledge of female technology entrepreneurship and its main factors and barriers associated with family, education, and financial access. A methodology with a quantitative approach was applied, using as a source of information a questionnaire for women entrepreneurs and creators of technology-based companies, which are mostly the ones who run their companies, and applying a method of descriptive analysis to identify the main factors and barriers that affect the creation of a business by women. This study was carried out in a territory of medium innovative performance such as the state of Atlántico, located in Colombia. The main results found in this research indicate that among the factors associated with the context, support for institutions that promote entrepreneurship play an important role Motivational factors include family support, knowledge of technology, and the search for independent autonomy. Regarding financial factors, it was found that women help themselves in their personal name and by participating in calls and/or contests. Finally, the network factors, it was obtained that women entrepreneurs participate in entrepreneurship ecosystems, are linked to business centers, and are supported by entrepreneurship groups and events. For the analysis of the barriers, it was concluded that time limitations and lack of skills are obstacles when starting a business, likewise, insufficient access to capital and insufficient access to financing are barriers that women have when they want to create a business. To conclude, it was found that when women want to create a business, they carry out their idea, however, it was possible to obtain that the very existence of context in terms of access to financing and limitations of the support instrument are barriers that have women at the time of creating a company. It should be noted that women recognize that family support is key in this entrepreneurial process.